2017
DOI: 10.1002/ccr3.1001
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in a splenectomized with β‐thalassemia major: immunocompetent or immunosuppressed?

Abstract: Key Clinical MessageWe should possibly revise our knowledge about risk assessment of splenectomized individuals with β‐thalassemia major. Besides their known risk of certain bacterial infection, they might be also in a risk of life‐threatening primary cytomegalovirus (CMV) infection and end‐, multi‐organ disease, in the context of their immunosuppression status. Prompt and appropriate treatment initiation can be life saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Many authors have underlined the problematic IgM response observed in primary CMV infection post-splenectomy. [16,20,21,23,25] A remarkable finding in half of our splenectomized cohort also was the low or totally absent anti-CMV IgM antibody titers, anytime tested during the disease course. Considering the numerous literature data mentioned above we could suggest 1 cardinal reason why splenectomized individuals are prone to primary CMV infection: the insufficient production of IgM antibodies in the absence of IgM IgD CD27 + subset of memory B-cells.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Many authors have underlined the problematic IgM response observed in primary CMV infection post-splenectomy. [16,20,21,23,25] A remarkable finding in half of our splenectomized cohort also was the low or totally absent anti-CMV IgM antibody titers, anytime tested during the disease course. Considering the numerous literature data mentioned above we could suggest 1 cardinal reason why splenectomized individuals are prone to primary CMV infection: the insufficient production of IgM antibodies in the absence of IgM IgD CD27 + subset of memory B-cells.…”
Section: Discussionmentioning
confidence: 68%
“…Another cardinal observation in our cohort that advocates the immunity defects of splenectomized against CMV is the mature B-cell lymphopenia, [17,20,24] the lowered T-helper (CD3 + CD4 + ), [17,1925] and the increased T-cytotoxic (CD3 + CD8 + ) [17,1921,2325] cells, with inversion of the CD4 + /CD8 + ratio. [1921,2325] The post-traumatic splenectomy results in a significant and long-term reduction of the levels of CD45RA + CD4 + T-cells which characterize the subset that has been released from the thymus into the periphery but has not yet encountered an antigen (naïve). [29] Marker analysis with monoclonal antibodies of the peripheral blood of splenectomized individuals revealed normal proportions except for CD4 + and B1 (peripheral B-cells) positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…All of them had a long period of high fever, severe interstitial pneumonitis with hypoxemia and marked lymphocytosis with numeral atypical lymphocytes as in our case. While writing this case report, another group published a similar case (6) by making these the first two cases of CMV pneumonitis in patients with β-thalassemia major and splenectomy.…”
Section: Textmentioning
confidence: 98%
“…Previous study revealed significant correlation between CMV infection and β-thalassemia major as red blood cells transfusions in beta-thalassemia major patients increase the probability of CMV infection which in turn cause severe thalassemia complications such reduction of phagocytic and chemotaxis activity of macrophages and neutrophils, reduction in the activity of lymphocytes, and changes in cytokines stimulation (Balouchi et al, 2014). Another study showed significant seroprevalence of CMV with high incidence infection (Liatsos et al, 2017;Nigro et al, 1990).…”
Section: Fig 3: Distribution Of Igm Igg-cmv and Cmv-dna In Age Groupsmentioning
confidence: 98%